Clinico-epidemiological investigation on Varicella Zoster Virus indicates multiple clade circulation in Maharashtra state, India. Issue 8 (August 2018) - Sahay, Rima R.; Yadav, Pragya D.; Majumdar, Triparna; Patil, Swapnil; Sarkale, Prasad; Shete, Anita M.; Chaubal, Gouri; Dange, Vinay R.; Patil, Savita; Nyayanit, Dimpal A.; Shastri, Jayanthi; Mourya, Devendra T.
Abstract: Background: Varicella Zoster Virus (VZV) is consistently in circulation and shows an increase in disease burden during the spring season. Due to a wide range of clinical presentation from a vesicular rash to bleeding or neurological complications, it makes the clinical diagnosis difficult. The present study aims to understand whether the same strain of virus is responsible for the increase in the seasonal outbreaks occurring in different parts of the country with reference to the samples from Maharashtra, Rajasthan and Gujarat states of India. Materials and methods: This study reports the clinico-epidemiological and laboratory findings of suspected Varicella cases. To understand the circulating clade few representative real-time Polymerase Chain Reaction (PCR) positive were analyzed by conventional PCR and partial Open Reading Frame (ORF) 22, partial ORF 38 and partial ORF 54 were sequenced to identify single nucleotide polymorphisms responsible for clade determination. Further partial glycoprotein B gene was sequenced, and a phylogenetic tree was generated. Results: A total of 50 cases from Maharashtra (Mumbai district) and referred clinical samples of Rajasthan (Barmer district; n = 12) and Gujarat States (Gandhi Nagar, Surat districts; n = 17) were tested for the presence of VZV. Vesicular rash with fever was a common clinical presentation with 82% cases having contact history with VZV positive cases, suggesting higher secondary attack rate. The vesicular fluid of all 50 cases from Mumbai revealed the presence of VZV by real-time PCR. Urine, serum and throat swab samples showed positivity by real-time PCR. Healthcare provider's samples from Rajasthan showed 36.4% [4/11] positivity. Clinical samples from Gujarat had positivity of 41.2% [7/17]. Conclusions: This study analyses the clade based circulation of VZV in three states in India and suggests different clades circulating in Maharashtra state. Health education amongst the general population is suggested to reduce the secondary cases by early diagnosis, effective isolation policies and vaccination to reduce the burden of disease.